On Twisting Real Spectral Triples by Algebra Automorphisms - Landi, Giovanni; Martinetti, Pierre (Letters in mathematical physics, 2016)
We systematically investigate ways to twist a real spectral triple via an algebra automorphism and in particular, we naturally define a twisted partner for any real graded spectral triple. Among other things, we investigate consequences of the twisting on the fluctuations of the metric and possible applications to the spectral approach to the Standard Model of particle physics.